The adhesion mechanism of mucoadhesive tablets with dissimilar chain flexibility on viscoelastic hydrogels - Gergely Stankovits; Kata Szayly; Dorián László Galata; János Móczó; András Szilágyi; Benjámin Gyarmati (Materials Today Bio)
Mucosal membranes with strong variability in their viscoelastic properties line numerous organs and are often targeted by mucoadhesive formulations, e.g., highly swellable hydroxypropylmethylcellulose (HPMC) and slightly cross-linked poly(acrylic acid) (PAA) tablets. Although the factors determining the strength of mucoadhesion are hierarchical and affected by both reversible and irreversible processes, the currently available strategies generally view mucoadhesion as the individual performance of the mucoadhesive excipient. We propose an integrated concept that considers the viscoelasticity and tensile properties of both the adhesive interphase and the bulk phases. To reduce the complexity of the mucosal membrane and eliminate the effect of specific macromolecular interactions, we studied the adhesion on mucosa-mimetic freeze/thawed (FT) poly(vinyl alcohol) (PVA) hydrogels. Their viscoelastic properties were controlled by the number of FT cycles and the polymer concentration. The adhesive strength of HPMC tablets displayed a pronounced dependence on the viscoelasticity of PVA gels, explained by the limited chain flexibility and interpenetration of HPMC, resulting in the formation of a thin the adhesive interphase compared to PAA. We recognized scaling laws between toughness and strength for tensile and adhesive properties as well as general correlations between viscoelastic and adhesive properties, which can aid the more rational design of both mucoadhesive formulations and mucosa-mimetic materials.